KETAATAN KEPADA PEMIMPIN DALAM PENETAPAN AWAL RAMADHAN DAN HARI RAYA DI INDONESIA MENURUT HADIST - Faisal Yahya (Fakultas Hukum Universitas Cut Nyak Dhien Langsa, 2017)
Abstract: The determination of the firts Ramadhan and Shawwal is always different in Indonesia, this is due to the many authorities that implement the determination. This paper examines the obedience to the government in the determining of first Ramadan and Holiday in Indonesia according to the hadist. After reviewing the hadits of early Ramadhan and holidays and also data on the determination of the firts Ramadhan and Shawwal by the Ministry of Religious of RI, it can be concluded that in the haditts perspective show that the government has autoriti in the determination of the beginning of Ramadhan and The holyday. So that Muslimsare ordered to perform the worship in a congregation. While in the context of Indonesia, the authority is not only given to the Ministry of Religious of RI but also to other institutions, therefore the observance of the results of the determination of Ministry of Religious Affairs is not an absolute.